2014
DOI: 10.1111/jcmm.12228
|View full text |Cite
|
Sign up to set email alerts
|

A loss of telocytes accompanies fibrosis of multiple organs in systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a complex connective tissue disease characterized by fibrosis of the skin and various internal organs. In SSc, telocytes, a peculiar type of stromal (interstitial) cells, display severe ultrastructural damages and are progressively lost from the clinically affected skin. The aim of the present work was to investigate the presence and distribution of telocytes in the internal organs of SSc patients. Archival paraffin-embedded samples of gastric wall, myocardium and lung from SSc pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 41 publications
7
113
0
1
Order By: Relevance
“…In addition, we found that in the normal cornea, TC establish homocellular contacts formed by gap junctions, highly specialized membrane structures which allow the exchange of small molecular mediators involved in intercellular signalling and thus contributing to the maintenance of tissue homoeostasis 38, 39. As suggested in other pathologies 23, 25, 26, 27, 28, 29, the reduction and loss of TC might therefore contribute to the altered organization of the ECM ultimately resulting into corneal dysfunction in keratoconus.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In addition, we found that in the normal cornea, TC establish homocellular contacts formed by gap junctions, highly specialized membrane structures which allow the exchange of small molecular mediators involved in intercellular signalling and thus contributing to the maintenance of tissue homoeostasis 38, 39. As suggested in other pathologies 23, 25, 26, 27, 28, 29, the reduction and loss of TC might therefore contribute to the altered organization of the ECM ultimately resulting into corneal dysfunction in keratoconus.…”
Section: Discussionmentioning
confidence: 59%
“…It is commonly believed that TC may play an important role in driving organ development and contributing to the maintenance of local tissue homoeostasis and, hence, TC damage and dysfunction may occur in several disorders 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 52, 53. In this context, we herein demonstrate that the normal morphological features and distribution of TC are severely compromised within the corneal stromal compartment in keratoconic pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown loss of telocytes in the gastric wall, myocardium and lung of SSc patients, suggesting that this loss may be implicated in the pathogenesis of fibrosis [11]. Recently, elevated levels of interleukin (IL)-33 have been correlated with the severity of skin and lung fibrosis [12].…”
Section: Pathogenesismentioning
confidence: 99%
“…TCs have been described in the interstitium of certain parenchimatous organs in mammals (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and, although ICCs have been identified in the digestive tract of turkeys (23) and in the intestine of chickens (24), the presence of ICLCs or TCs in the digestive system of the chicken remains unclear. In addition, Cantarero Carmona et al (25) described TCs at the intestinal level, in the lamina propria of rat duodenum; however, to the best of our knowledge, studies on TCs in the intestinal muscularis have not previously been conducted.…”
Section: Introductionmentioning
confidence: 99%